Museum Exhibitions of Fossil Specimens Into Commercial Products: Unexpected Outflow of 3D Models due to Unwritten Image Policies - Matsui, Kumiko; Kimura, Yuri (Frontiers in Earth Science, 2022)
Recent innovations and cost reductions in photogrammetry-based 3D modeling have enabled museum visitors to create 3D models based on photographs exhibited in galleries without breaking museum policies. While several museums make 3D museum data available on sharing platforms, museum visitors publish unofficial 3D data belonging to museum exhibits using a photogrammetry-based approach. This study shows that photogrammetry-based 3D models can be generated without breaking conventional photo policies (i.e., no use of flash and tripods) and that museum visitors can create commercial products based on these models. 3D models certainly enhance scientific value and promote broader and deeper interests in the natural sciences; however, the rights of owners of museum pieces are ambiguous with regard to the dissemination of unofficial data. This also makes information attributable to the original specimen unclear, which can potentially lead to revenue loss. We propose a set of best practices for museum photo policies covering the data use of visitor-generated 3D models of displayed objects.